Theories of terrorism an introduction - Pisoiu, Daniela; Hain, Sandra (Routledge, Taylor & Francis Group, 2018)
The book identifies the main theories proposed in the field of terrorism studies as they relate to several issues: why and how individuals and organizations get involved in terrorism; the definition and concept of terrorism; state terrorism; leaving terrorism behind; counter-terrorism; manifestations of terrorism in time and space. This book will be essential reading for students of terrorism studies, political violence, and counter-terrorism, and is highly recommended for students of security studies, criminology, politics, and international relations.